2019
DOI: 10.5720/kjcn.2019.24.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Nutrition Status and Metabolic Syndrome Prevalence of the Members according to the Number of Household Members based on the Korea National Health and Nutrition Examination Survey (2013–2014)

Abstract: Objectives: This study evaluated the nutritional status and prevalence of metabolic syndrome of the people who participated in the KNHANES according to the number of household members. They were assessed by using information from the 2013∼2014 Korea National Health and Nutrition Examination Survey (KNHANES).Methods: A total of 6,088 persons aged 19 years and over participated in 2013∼2014 KNHANES, and they were classified into three groups according to the number of household members (single-person, two-person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Fourth, DRI methods can be biased by within-individual variance [ 34 ]. Notably, DRI methods tend to lead to biased estimates, as supplementary consumption sources can compensate for daily nutrient intake from regular food sources.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, DRI methods can be biased by within-individual variance [ 34 ]. Notably, DRI methods tend to lead to biased estimates, as supplementary consumption sources can compensate for daily nutrient intake from regular food sources.…”
Section: Discussionmentioning
confidence: 99%
“…While rapid changes in the population structure are causing fundamental changes in society, economy, and culture, the increase in single-person households has led to drastic changes in daily life, such as residential environment, consumption structure, and dietary habits 21) . Risk factors overlap 22) , and substantial health-care assistance is necessary due to the poor living conditions of single-person households, which have relatively poor lifestyles compared to multi-person households. Thus, this study was conducted to examine the oral health in single-person households with metabolic syndrome, which has been linked to various lifestyle factors, including dietary habits 23) and to determine their effect on the risk of developing metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported a significant disparity in nutrient intake between single-person households and multi-person households, which has worsened with increasing age and decreasing income [ 11 ]. In contrast to multi-person households with two or more family members, single-person households have a low-quality diet and inadequate intake of protein, dietary fiber, calcium, phosphorus, vitamin A, thiamin, riboflavin, niacin, and vitamin C [ 12 ]. Furthermore, single-person households spend a greater percentage of their income on food compared with multi-person households.…”
Section: Introductionmentioning
confidence: 99%